Investment optimization for APEC member countries (economic studies & challenge of DPMPTSP-DKI Jakarta) - Budya Pryanto Putra; Aleknaek Martua Nababan (Monas: Jurnal Inovasi Aparatur, 2019)
Foreign Direct Investment (FDI) is one of the economic indicators that is currently getting special attention from the government. This is because the presence of Foreign Direct Investment has a direct and indirect influence on economic performance in a country. The purpose of this analysis is to find out how big the role of indicators of ease of doing business, especially the starting a business and dealing with construction permits, which was initiated by the World Bank in influencing Foreign Direct Investment on APEC member countries. The method of this study is a causal relationship with multiple linear regression analysis using the Generalized Method of Moments to estimate the parameter. The results obtained from this analysis are that the starting a business has a considerable role in foreign direct investment in addition to the economic control variables in the form of Real GDP, Labor Force, and Human Development Index. The conclusion of this study is starting a business and the Human Development Index has a very vital role in the development of investment for the Asia Pacific region.